2012
DOI: 10.1055/s-0031-1299721
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep Instability – A New Pathway for Insomnia?

Abstract: Chronic insomnia afflicts approximately 10% of the adult population and is associated with daytime impairments and an elevated risk for developing somatic and mental disorders. Current pathophysiological models propose a persistent hyperarousal on the cognitive, emotional and physiological levels. However, the marked discrepancy between minor objective alterations in standard parameters of sleep continuity and the profound subjective impairment in patients with insomnia is unresolved. We propose that "instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
181
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(198 citation statements)
references
References 127 publications
11
181
1
5
Order By: Relevance
“…To do so, we systematically evaluated the association of all items of the NSR's extended implementation of the Dream Recall Frequency Scale (DRFS; Methods) (30) with the REM sleep arousal index (31) obtained from the second of two nights of PSG in 32 people [19 female and 13 male, mean (SD) of 35.8 (9.0) y of age], of whom 16 had been diagnosed with Insomnia Disorder (ID). Metaanalysis showed that variables reflecting disruption of sleep continuity are the most robust PSG signatures in insomnia (16), especially fragmentation of REM sleep (5,17). Although less specific to insomnia, fragmentation occurs in NREM sleep as well (5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To do so, we systematically evaluated the association of all items of the NSR's extended implementation of the Dream Recall Frequency Scale (DRFS; Methods) (30) with the REM sleep arousal index (31) obtained from the second of two nights of PSG in 32 people [19 female and 13 male, mean (SD) of 35.8 (9.0) y of age], of whom 16 had been diagnosed with Insomnia Disorder (ID). Metaanalysis showed that variables reflecting disruption of sleep continuity are the most robust PSG signatures in insomnia (16), especially fragmentation of REM sleep (5,17). Although less specific to insomnia, fragmentation occurs in NREM sleep as well (5).…”
Section: Resultsmentioning
confidence: 99%
“…resolving of emotional distress and whether hyperarousal, in fact, represents the resulting accumulation of this distress. Of note, hyperarousal is not only present across waking and sleep in people suffering from MDD (21) but is also of key importance in the pathophysiology of primary insomnia (6,(22)(23)(24) and a premorbid characteristic of people vulnerable to insomnia (5,25).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…comorbid insomnia; a common symptom in PD. Riemann et al (Riemann et al, 2012) reports REM sleep instability as an objective measure for primary insomnia patients compared to good sleeper controls. Although they measure REM sleep instability differently than us (number of manually scored micro-arousals and awakenings per hour of REM sleep compared to our fully data-driven method), we cannot rule out insomnia as causative for the lower REM sleep stability.…”
Section: Discussionmentioning
confidence: 99%